DEIXIS INACCUARY IN THE UTTERANCES OF WERNICKE’S APHASIA SUFFERERS ON YOUTUBE CHANNELS - Dewi Karimah; Rohmani Nur Indah (Universitas Pamulang, 2022)
In the utterances of Wernicke's aphasia sufferers, there are deixis inaccuracy or errors that can make the interlocutor unable to understand the meaning of Wernicke's aphasia sufferers. Existing research on deixis is still limited to ordinary people's speech, so in-depth research is needed on deixis in the utterance of Wernicke's aphasia sufferers, especially on deixis errors. Therefore, this study aims to identify the types and analyze the meaning of deixis errors expressed by Wernicke's aphasia sufferers. The deixis errors were identified from the utterances produced by four Wernicke's aphasia sufferers on YouTube channels. Data retrieval is in the form of choosing a few words that are only included in the expression of the use of deictic errors identified according to Levinson (1983). After that, the utterances containing deixis errors were interpreted from the context and the typology of the inaccuracy. The finding shows three out of five types of deixis errors made by Wernicke's aphasia sufferers. The most dominant type of deixis errors found is personal deixis. The results of this study can be helpful for further research to examine deixis errors in the speech of Wernicke's aphasia sufferers across different severity, language choice, age, gender and others. In addition, those who have interaction with Wernicke aphasia are supposed to provide easy-to-understand questions to avoid more occurrences of deixis inaccuracy.